Synthesis of Quinoline Derivatives by Multicomponent Reaction Using Niobium Pentachloride as Lewis Acid - Andrade, Aloisio de [UNESP]; Santos, Giovanny Carvalho dos [UNESP]; Silva-Filho, Luiz Carlos da [UNESP] (Wiley-Blackwell, 2015)
The aim of this work was to investigate the use of NbCl5 as a Lewis acid in multicomponent reactions between benzaldehyde, aniline derivatives and phenylacetylene in the synthesis of quinoline derivatives. The effects of the temperature and substituents in the aromatic ring of the aniline were also evaluated. The reactions were carried out at low concentration of niobium and in relatively short reaction times, resulting in yields ranging from 67 to 96%.